2000
DOI: 10.1046/j.1523-1739.2000.99079.x
|View full text |Cite
|
Sign up to set email alerts
|

Cougar Dispersal Patterns, Metapopulation Dynamics, and Conservation

Abstract: We examined cougar (  Puma concolor) dispersal, emigration, and immigration in the San Andres Mountains, New Mexico, from 1985 to 1995 to quantify the effects of dispersal on the local population and surrounding subpopulations. We captured, tagged, and radio‐collared animals to detect the arrival of new immigrants and dispersal characteristics of progeny. We found that cougars in southern New Mexico exhibited a metapopulation structure in which cougar subpopulations were separated by expanses of noncougar habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
236
3
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(273 citation statements)
references
References 25 publications
19
236
3
6
Order By: Relevance
“…Indeed, Beckmann and Lackey (2004) concluded that desert matrix was not an effective barrier to bear movement in the Great Basin of Nevada. We found for black bears in our study region, as observed for cougars in other Chihuahuan desert habitats (Sweanor et al, 2000), that we could not identify distinct corridors for dispersal between insular mountain ranges.…”
Section: Implications To Carnivore Conservationcontrasting
confidence: 68%
See 2 more Smart Citations
“…Indeed, Beckmann and Lackey (2004) concluded that desert matrix was not an effective barrier to bear movement in the Great Basin of Nevada. We found for black bears in our study region, as observed for cougars in other Chihuahuan desert habitats (Sweanor et al, 2000), that we could not identify distinct corridors for dispersal between insular mountain ranges.…”
Section: Implications To Carnivore Conservationcontrasting
confidence: 68%
“…Dispersal by male mountain lions in the anthropogenically-constrained regions of southern California (x = 63 km; Beier, 1995) and southern Florida (x = 68 km; Maehr et al, 2002) is approximately 50% of that reported for the species in the naturally fragmented Chihuahuan desert (x = 116 km; Sweanor et al, 2000). Similarly, Boyd and Pletscher (1999) stated variability in wolf (Canis lupus) dispersal may be a function of human density and landscape patchiness, among other factors.…”
Section: Implications To Carnivore Conservationmentioning
confidence: 87%
See 1 more Smart Citation
“…Six unconfirmed Yukon sighting records include kittens (Yukon Department of Environment, unpublished data), suggesting a breeding population. Alternatively, Cougars seen in the Yukon may represent a few individuals (e.g., young males) that make long distance dispersals and are not indicative of a viable local breeding population (Pierce et al 1999;Sweanor et al 2000). In Wyoming, one radio-collared male Cougar is known to have dispersed >1000 km (Thompson and Jenks 2005).…”
mentioning
confidence: 99%
“…En uno de ellos se asoció el 82 % de los individuos de la costa norte de California y en el otro el 87 % de los individuos del suroeste de California. Esto es, en ciertas áreas de la distribución de su rango, las poblaciones de pumas parecen seguir una estructura metapoblacional (Beier 1996, Sweanor et al 2000, pero en otras zonas los animales muestran desplazamientos extremadamente largos (Pierce et al 1999) Obviamente, las estimas de flujo génico entre la muestra boliviana y las de otros países del entorno fueron ostensiblemente superiores (para F ST , Nm = 6-22; para R ST, Nm = 3-5; para alelos privados, Nm = 1,29) a las reportadas para las poblaciones de Texas (para F ST , Nm = 2,07; para R ST, Nm = 0,625; para alelos privados, Nm = 0,545). Estas estimas están basadas en la asunción de un modelo WrightFisher con equilibrio deriva-flujo génico (no para el procedimiento de los alelos privados) que probablemente no se da para las poblaciones de pumas estudiadas, lo que podría ofrecer estimas de flujo génico no concordantes con la realidad.…”
Section: ¿Existen Diferentes Subespecies De Puma En El áRea Geográficunclassified